2012
DOI: 10.1124/jpet.112.194662
|View full text |Cite
|
Sign up to set email alerts
|

Copper Is Required for Cobalt-Induced Transcriptional Activity of Hypoxia-Inducible Factor-1

Abstract: Cobalt inhibits prolyl hydroxylases, leading to the accumulation of hypoxia-inducible factor-1␣ (HIF-1␣) and a concomitant increase in the transcriptional activity of HIF-1. Therefore, cobalt has been under development as a drug for activating HIF-1 under some disease conditions. However, it has been shown that ischemic conditions resulted in the loss of copper, and the activation of HIF-1 would not occur unless copper was supplemented. The present study was undertaken to test the hypothesis that copper is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 31 publications
2
64
0
2
Order By: Relevance
“…1) [23]. A recent study on HUVEC cultures further confirmed that copper does not significantly affect endothelial HIF-1α accumulation, but the related transcriptional activity is impaired when intracellular metal availability/trafficking is depressed [26]. This concept is sustained by a bulk of literature showing that ischaemic heart tissue suffers from poor copper content, despite abundant HIF-1α levels [27].…”
Section: Copper Tunes the Activity Of Several Pro-angiogenic Factorsmentioning
confidence: 50%
“…1) [23]. A recent study on HUVEC cultures further confirmed that copper does not significantly affect endothelial HIF-1α accumulation, but the related transcriptional activity is impaired when intracellular metal availability/trafficking is depressed [26]. This concept is sustained by a bulk of literature showing that ischaemic heart tissue suffers from poor copper content, despite abundant HIF-1α levels [27].…”
Section: Copper Tunes the Activity Of Several Pro-angiogenic Factorsmentioning
confidence: 50%
“…A number of studies have investigated the stimulatory action of copper on VEGF production and tumor angiogenesis [36,41,59] as well as the repressive effects exerted by copper-chelating on HIF-1α mediated expression of VEGF [60,61].…”
Section: Vegf73-101 But Not Vegf84-101 Induces Apoptosis In Huvecmentioning
confidence: 99%
“…85 According to recent studies, cobalt-induced stabilization of Hif-1α is dependent on copper. 86,87 Furthermore, copper supplementation reversed contractile dysfunction and prevented transition to heart failure in pressure-overloaded mice, at least in part through promotion of myocardial angiogenesis. 88 In addition to cobalt and copper function, several approved drugs have been reported to affect myocardial angiogenesis.…”
Section: Therapeutic Myocardial Angiogenesis As a Potential Therapy Fmentioning
confidence: 99%